Improving the Care of Dual Eligible Patients in Rural Federally Qualified Health Centers: The Impact of Care Coordinators and Clinical Pharmacists. (April 2016) - Doyle, Daniel; Emmett, Mary; Crist, Amber; Robinson, Craig; Grome, Michael
Background: Dual eligible persons are those covered by both Medicare and Medicaid. There were 9.6 million dual eligible persons in the United States and 82 000 in West Virginia in 2010. Dual eligibles are poorer, sicker, and more burdened with serious mental health conditions than Medicare or Medicaid patients as a whole. Their health care costs are significantly higher and they are more likely to receive fragmented ineffective care.Purpose: To improve the care experience and health care outcomes of dual eligible patients by the expanded use of care coordinators and clinical pharmacists.Methods: During 2012, 3 rural federally qualified community health centers in West Virginia identified 200 dual eligible patients each. Those with hospitalizations received more frequent care coordinator contacts. Those on more than 15 chronic medications had drug utilization reviews with recommendations to primary care providers. Baseline measures included demographics, chronic diseases, total medications and Beers list medications, hospitalization, and emergency room (ER) use in the previous year. Postintervention measures included hospitalization, ER use, total medications, and Beers list medications.Results: Out of 556 identified patients, 502 were contacted and enrolled. Sixty-five percent were female. The median age was 69 years, with a range of 29 to 93 years. Nineteen percent (19%) of patients were on 15 or more medications, 56% on psychotropic medication, and 33% on chronic opiates. One site showed reductions of 34% in hospitalizations and 25% in ER visits during the intervention year. For all sites combined, there was a 5.5% reduction in total medications and a 14.8% reduction in Beers list medications.Conclusions: A modest investment in care coordination and clinical pharmacy review can produce significant reductions in hospitalization and harmful polypharmacy for community dwelling dual eligible patients.